PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN BERAS PUTRI KOKI PREMIUM DI KABUPATEN JEMBER - Al-Ardi, Aditya Nizar; Nadhirah, Aulia; Saadillah, Dinu; Sutantio, Alamsyah (Journal of Agricultural Socio-Economics (JASE), 2024)
Consumer satisfaction plays an important role in expanding the marketing area of a product brand. Consumer satisfaction can be determined by the suitability of the quality of the product and also the price received by consumers. Putri Koki Premium Rice can currently dominate the rice market in Jember Regency. Based on this statement, this research was conducted to find out how much product quality and price can influence consumer satisfaction for Putri Koki Premium rice in Jember Regency. Multiple regression analysis was used in this research and the sample was 100 respondents who were consumers of Putri Koki Premium rice. The results of calculations using SPSS software state that the quality and price variables of Putri Koki Premium rice jointly and partially have a significant effect on consumer satisfaction. The coefficient of determination value obtained was 70.3%.